Hans Kelsen on legal interpretation, legal cognition, and legal science. (3rd April 2019) - Paulson, Stanley L.
ABSTRACT: As the title suggests, I take up three motifs in the article. Legal science, on a narrower reading, examines the law qua object of legal cognition. Substituting legal cognition for traditional legal interpretation, Kelsen claims that legal cognition is constitutive of its object, a claim that requires a neo-Kantian transcendental argument for support. The rub comes with legal norms that fail to satisfy the conditions ostensibly imposed by legal cognition, for they, too, pass muster. They, too, are legally valid, raising serious questions about the status of the neo-Kantian dimension of Kelsen's Pure Theory of Law. I address these questions in my concluding remarks.